PWE-142 Is Liver Disease Overlooked In Patients With Psoriasis?. (9th June 2014) - Ooi, J; Chinthapalli, S; O'Toole, E; Alazawi, W
Abstract : Introduction: Elevated transaminases (e.g., ALT) are frequently identified in various medical specialties, but the significance of abnormalities is often unclear. Patients with psoriasis are at higher risk of abnormal ALT due to drug-induced liver toxicity and alcohol excess. Recent reports highlight the association of psoriasis with metabolic syndrome, and suggest that non-alcoholic fatty liver disease (NAFLD) is more common in patients with psoriasis compared to the general population. Our aim was to determine (1) the prevalence and extent of raised ALT in a psoriasis clinic, (2) the degree to which such abnormalities are investigated and (3) the common causes identified. Methods: We undertook a retrospective analysis of adult patients with psoriasis followed up at the Royal London Hospital between Aug-Nov 2013. Electronic records were searched for demographics, blood results, hepatological investigations, psoriasis treatments, metabolic risk factors (diabetes, dyslipidaemia, hypertension, obesity), and alcohol intake. Elevated ALT was defined as >40 U/L for men, >35 U/L for women. The FIB-4 score was calculated to estimate risk of fibrosis. Results: Electronic records for 200 patients with psoriasis were reviewed. 57% (n = 114) were male, median age 43 years (range 17–81). 48% were Caucasian, 22% Bangladeshi, 12% Indian, 6% Pakistani and 6% Afro-Caribbean. LFTs were performed in 80.5% of patients (n = 161), of whom 37% (n = 59) had abnormal ALT on ≥2 occasions (mean peak ALT 91, SD 63). 9 of these patients were on medication associated with deranged LFTs (4 on acitretin; 5 on methotrexate with persistently raised PIIINP). A further 15 patients drank excess alcohol. 3 patients (5% of 21 tested) had viral hepatitis (1 HBV, 2 HCV). Of the remaining 32 with unexplained elevated ALT, only 8 patients had a liver ultrasound (25%), of whom 4 had signs of NAFLD. In addition, it is probable that another 17 patients who had negative liver screens but not had an ultrasound also have NAFLD. Therefore the estimated prevalence of NAFLD among psoriasis patients with raised ALT is 36% (21/59). There was no significant difference in age, sex or ethnicity between this group and the total psoriasis population. Sufficient data were available to calculate FIB-4 scores in 12 of these 21 patients. 2 had scores that suggest moderate or advanced fibrosis, and warrant further investigation. Conclusion: Patients with psoriasis often have LFTs measured. These are often abnormal but under-investigated despite potentially representing significant, treatable disease. We identified a gap between LFT testing and screening for liver diseases, particularly viral hepatitis and NAFLD. There is a need for evidence-based guidance on investigation and referral in patients with deranged LFTs. Disclosure of Interest: None Declared.